Global warming at the east coast zone of Peninsular Malaysia - Mohamed Shaffril, Hayrol Azril; Abu Samah, Bahaman; D'Silva, Jeffrey Lawrence; Uli, Jegak (Science Publications, 2011)
Problem statement: Global Warming is not a new phenomenon and it is already been felt by people all around the world. Not only the people affected by the global warming, but also our sea. There are a lot of potential threats that can be caused by global warming on the sea such as rise of sea level, changes in waves action, water current and wind velocity, but do one of the main users of the sea which are the fishermen have already felt these impacts? Approach: This is a quantitative study where a developed questionnaire was used to gain the data needed. Through a stratified random sampling a total of 300 registered fishermen from four states in the east coast zone of Peninsular Malaysia namely Kelantan, Terengganu, Pahang and East Johor have been selected. Results: This study provided a greater understanding of the fishermen views on the changes that happened to the sea due to the global warming impact. They stressed that the temperature, the rainfall season and the coastal areas have changed. Furthermore, according to them, the sea nowadays are no longer easy to predict as the water current, wind velocity and wave’s actions can easily change their pattern and endanger them while they are at the sea. Conclusion/recommendation: Effective actions can be taken to assist the fishermen to adapt to impacts of global warming. One of it is to provide them with more information on global warming. Besides, fishermen in Malaysia also can be provided with trainings in order to provide them with other skills besides fishing.